Problematika Administrasi Sarana dan Prasarana pada Lembaga Pendidikan Islam di Indonesia - Widya Alfa Rizky; Ahmad Sabri; Yusran Lubis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Educational administration is the entire process of working together by utilizing all available and needed resources to achieve educational goals that have been set effectively and efficiently. Educational administration is basically administration in processing, organizing and allocating the resources contained in the world of education. Facilities are all the facilities needed in the teaching and learning process, both moving and immovable, so that educational goals can be achieved and run smoothly, regularly, effectively and efficiently. Meanwhile, the definition of infrastructure is facilities that indirectly support the course of the educational process, such as; yard, garden or school garden, road to school, school rules, and so on. Administration of educational facilities and infrastructure is something that really supports the achievement of the goals of education, as education personnel we are required to master and understand the administration of facilities and infrastructure, to increase effective and efficient work power and be able to respect the work ethics of fellow educational personnel, so that harmony and comfort will be created which can create pride and a sense of belonging from both the school community and the surrounding community.